To find angle A, we need to solve the equation 2sin^2 A - 1/3 = A.
Let's first rearrange the equation to get it in the form of a quadratic equation in terms of sin A:
2sin^2 A - 1/3 = A
2sin^2 A = A + 1/3
sin^2 A = (A + 1/3) / 2
sin A = ±√((A + 1/3) / 2)
(sin A)^2 = (A + 1/3) / 2
Since A is acute, sin A is positive. Therefore:
sin A = √((A + 1/3) / 2)
Squaring both sides gives us:
sin^2 A = (A + 1/3) / 2
(A + 1/3) / 2 = sin^2 A
Now, we know that sin^2 A = 1 - cos^2 A (from trigonometric identity), so we can write:
(A + 1/3) / 2 = 1 - cos^2 A
A + 1/3 = 2 - 2cos^2 A
cos^2 A = 1 - (A + 1/3)/2
cos A = ±√(1 - (A + 1/3)/2)
cos A = ±√((2 - A - 1/3)/2)
cos A = ±√((5/3 - A)/2)
Since A is acute, cos A is positive, so:
cos A = √((5/3 - A)/2)
Now, using the fact that sin^2 A + cos^2 A = 1, we can square and sum the equations for sin A and cos A:
(sin A)^2 + (cos A)^2 = 1
((A + 1/3) / 2) + ((5/3 - A)/2) = 1
(A + 1/3 + 5/3 - A) / 2 = 1
2/2 = 1
1 = 1
Since the sum of the squares of sin A and cos A equals 1, we have a valid solution for angle A.
Therefore, angle A satisfies the equation 2sin^2 A - 1/3 = A.
Given that Ais acute and 2sin^2 A -1/3 A, find angle A.
1 answer